DEVELOPMENT AND VALIDATION OF INSTRUMENT FOR ASSESSING PERCEPTION OF STUDENTS ON ACADEMIC REPUTATION OF UNIVERSITIES IN NORTH-EAST, NIGERIA - Michael, Happy Linda; Amuche, Chris Igomu; Obiji, Donatus (African Journal of Behavioural and Scale Development Research, 2024)
The study developed and validated an instrument for assessing students’ perception of academic reputation of universities in North-East, Nigeria. Three research questions were answered in the study. The study adopted an instrumentation design. The population of the study comprised undergraduate students in North-East Nigeria public universities. A sample size of 1058 students was selected from four universities in the zone, using multi-stage sampling procedures. A developed questionnaire titled “UARS” was used for data collection. The face and content validity of the instrument was ensured through experts’ judgment. Content validity index of 0.76 was obtained for UARS. Exploratory factor analysis was carried out to determine the underlying components of the scale through principal components analysis (PCA) with varimax rotation while the confirmatory factor analysis was applied to determine the convergent and discriminant validity of the instrument. Guttman split-half, Cronbach coefficient alpha and Feldt Gilmer methods were used to establish the reliability of UARS. Findings showed that five components underlined the scale. The average variance extracted (AVE) values for the constructs were above 0.5 each, while the respective square roots are higher than the inter-constructs correlation values. This implies that the constructs are distinct from one another and their traits converge to measure the same factor. The reliability index of UARS was 0.92 which indicates that the instrument is excellent. Having established the validity, reliability and suitability of UARS, it was therefore recommended that researchers, university administrators, policymakers and regulatory bodies intending to assess students’ perception of academic reputation of universities, should use the five components identified in the study. Also, the instrument should be used in North-East and other geo-political zones in Nigeria, to enhance the academic quality of our universities.